Association of blood lead and homocysteine levels among lead exposed subjects in Vietnam and Singapore. Issue 10 (20th April 2007) - Chia, Sin Eng; Ali, Safiyya Mohamed; Lee, Bee Lan; Lim, Gek Hsiang; Jin, Su; Dong, Nguyen-Viet; Tu, Nguyen Thi Hong; Ong, Choon Nam; Chia, Kee Seng
Abstract : Objectives: Lead and homocysteine are both linked to cardiovascular disease. With this in mind, the authors evaluated the relation between blood lead and homocysteine in people aged 19–66 years in two Asian populations. Methods: This cross-sectional study comprised 183 workers from a lead stabiliser factory in Singapore and 323 workers from a battery factory in Vietnam. Workers were occupationally exposed to lead. Blood lead was analysed using atomic absorption spectrophotometry while plasma homocysteine was measured using high performance liquid chromatography. Results: Chinese subjects had the lowest blood lead levels while the Indians had the highest. Controlling for age, sex and race, an increase of 1 μg/dl in blood lead was associated with an increase of 0.04 μmol/l of homocysteine on the log scale. Gender and ethnicity seemed to be strongly associated with the relation between lead and homocysteine. The positive relation between lead and homocysteine among the Vietnamese subjects was significant (Pearson's r = 0.254, p<0.01). When blood lead levels were divided by quartiles, the correlation coefficient between blood lead levels in the 4th quartile and homocysteine among the Vietnamese was higher (r = 0.405, p<0.01). Overall, an increase of 1 μg/dl in blood lead in all the Vietnamese subjects was associated with an increase of 0.05 μmol/l increase in homocysteine on the log scale. However, in the 4th quartile, the same increase was associated with an increase of 0.41 μmol/l of homocysteine on the log scale. Conclusions: Blood lead was found to be associated with homocysteine levels in this Asian sample. Although we cannot determine causality from cross-sectional data, it is sensible to consider the probability that this relation could explain one of the mechanisms of the impact of lead on the cardiovascular system. More studies would be needed to confirm this inference.